Household Composting Innovation as a Participatory Solution for Waste Management: Strengthening Environmental Literacy through Household Composting - Fitri Widiastuti; Parmadi Parmadi; Yohanes Vyn Amzar; Dwi Hastuti; Helen Parkhurst (Borneo Research and Education Center, 2026)
This community service program aimed to improve environmental literacy and household waste management practices through participatory household composter innovation in Teluk Nilau Village, Tanjung Jabung Barat Regency, Jambi Province. The activity employed a Participatory Action Research (PAR) approach involving 35 participants consisting of housewives, youth groups, and community leaders. The program was conducted from August to September 2025 through problem identification, environmental education, composter training, mentoring, monitoring, and evaluation stages. Data were collected using observation sheets, interviews, pre-test and post-test instruments consisting of 15 indicators related to environmental literacy and waste management behavior. The results demonstrated significant improvement in participants’ understanding and behavior. Knowledge regarding organic and inorganic waste classification increased from 30% to 70%, understanding 3R principles increased from 25% to 65%, household waste sorting behavior increased from 20% to 60%, and composting skills increased from 10% to 50%. The program also succeeded in establishing environmental cadres and initiating household compost production with economic value. This activity indicates that participatory-based waste management can strengthen environmental awareness, encourage behavioral transformation, and support sustainable community-based economic development in coastal areas.